Teacher Training and Assistance of Flipped Learning Integration for School - Yeasy Agustina Sari; Wawan Wawan; Mai Zuniati; Windarsih Windarsih; Ikhwan Aziz; Mispani Mispani (CV. Creative Tugu Pena, 2023)
This article aims to give an assistance of teachers increasing knowledge and experience linked to the implementation of flipped learning models and the necessary technological support, as well as support so that instructors can use the flipped learning model in practical settings. Teachers from a variety of levels and courses work with this program as partners. This service is provided in the province of Lampung with the assistance of teachers at IAIMNU Metro Lampung and some schools. The method used Asset-Based Community Development (ABCD). The training and workshops are used to carry out activities. This activity was held at the IAIMNU Hall of Metro, and 34 people were present, that conducted on October 25, 2021, The basic task of this activity is to provide information and scientific understanding regarding the use of technology-integrated Flipped Learning. Additionally, the session included instruction on utilizing Bandicam to create video presentations. Wawan, M.P.D. and Mai Zuniati, M.P.D. presented this set of activities with the aid of various pupils. After the training, participants were asked if they understood the information, and the findings of the survey on comprehending the content revealed that 61.8% and 14.7%, respectively, said they did. Regarding the usefulness factor, 52.9% and 35.3%, accordingly, of the training's participants reported that it was useful. Keywords: Assistance of Flipped Learning, Training Flipped Learning, Learning for School